2022
DOI: 10.26677/tr1010.2022.1086
|View full text |Cite
|
Sign up to set email alerts
|

Elektronik Spor Turizmi: Elektronik Spor İzleyicileri Üzerine Bir Araştırma (Electronic Sports Tourism: A Study on Electronic Sports Audiences)

Abstract: Elektronik spor, çevrimiçi oyun ve karşılaşmalarla birlikte fiziksel olarak düzenlenen etkinlikleri de kapsayan çok boyutlu bir kavramdır. Elektronik spor izleyicilerinin yakından takip ettikleri etkinlikler, ev sahibi şehirlere sosyal ve ekonomik açıdan önemli katkılar sağlama potansiyeline sahiptir. Etkinliklere katılan izleyiciler, diğer tüm turistler gibi konaklama, yeme-içme, ulaşım, eğlence imkanlarından yararlanmaktadır. Bu durum elektronik spor etkinliklerinin turizm sektörü açısından değer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…income status of sports science students and the pre-test post-test mean scores of the participants from the "Future Expectation" scale. Yıldırım and Özkan [20] found that there was no significant difference between the variables of gender. age.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…income status of sports science students and the pre-test post-test mean scores of the participants from the "Future Expectation" scale. Yıldırım and Özkan [20] found that there was no significant difference between the variables of gender. age.…”
Section: Discussionmentioning
confidence: 94%
“…age. department and income status of sports science students and the pretest and posttest scores of the participants from the "Future Expectation" scale [20].…”
Section: Discussionmentioning
confidence: 99%